Integrating 3D Technology into Garment Pattern-Making: Effects on Learning Outcomes - Qiao, Danqing (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study examines the effects of integrating 3D technology into garment pattern-making education within a vocational education context. Research design, data and methodology: A quasi-experimental design was implemented with 88 first-year students in China, divided equally into a Style3D-assisted experimental group and a control group taught through traditional methods. Both groups completed identical instructional content, while learning outcomes were measured through standardized academic tests, a spatial visualization assessment, and a post-intervention engagement survey. Results: Findings indicate that the experimental group achieved significantly higher scores in applying knowledge, analyzing garment structures, and developing Apparel Spatial Visualization Skills, whereas no significant differences were observed in remembering or understanding. Qualitative reflections further revealed stronger engagement among experimental group students, including higher motivation, sustained focus, and improved conceptual clarity. These results demonstrate that 3D-assisted instruction is particularly effective for fostering higher-order cognitive skills and spatial reasoning, while traditional approaches remain important for reinforcing foundational knowledge. Conclusions: The study highlights the pedagogical value of blended instruction that combines digital simulation with manual drafting. Such integration supports both technical skill development and conceptual understanding, preparing vocational learners for the digital transformation of the fashion industry.